Interações planta-polinizador em vegetação de altitude na mata atlântica - Wolowski, Marina; Nunes, Carlos Eduardo Pereira; Amorim, Felipe W. [UNESP]; Vizentin-Bugoni, Jeferson; Aximoff, Izar; Maruyama, Pietro Kiyoshi; de Brito, Vinicius Lourenço Garcia; Freitas, Leandro (Oecologia Australis, 2016)
Tropical high-altitude vegetation is unique due to susceptibility to severe weather conditions in relation to lower formations, and by the peculiarity of its flora with many relictual components. Studies on plant-pollinator interactions in high-altitude rocky outcrops and forests of the Atlantic Forest are scarce, but compilation of information allows us to identify some patterns: low frequency of visits, high floral longevity and generalized pollination system. In tropical mountain ecosystems, the degree of generalization of pollination systems in functional (pollinator groups) and ecological (number of species) terms tends to be high, mainly due to the over-representation of certain plant taxa (e.g., Asteraceae in rocky outcrops and Fabaceae, Myrtaceae, Rubiaceae and Sapindaceae in montane forests). Generalized pollination systems and autogamy may be advantageous for tropical high-altitude plants due to the more severe weather conditions (e.g., low temperature), which decrease abundance and limit the activity of pollinators, resulting in lower visitation frequency. Nevertheless, some well represented groups in forests, such as orchids and plants pollinated by hummingbirds and bats, exemplify cases of higher functional specialization, as well as plants with poricidal anthers pollinated by bees in the high-altitude grasslands. However, in rocky outcrops, for some functional groups of pollinators (e.g., hummingbirds, bats, beetles and hawkmoths), the availability of resources does not allow the maintenance of all species throughout the year, favoring possible local or altitudinal migrations. Thus, rocky outcrops and high-altitude forests constitute a unit in the sense of sustaining the pollinator community. Indeed rocky outcrops and high-altitude forests share an evolutionary history at the regional scale since they passed through similar events of expansion and retraction in response to climate changes in the Quaternary. This could explain the complementarity between the two types of vegetation in the use of floral resources by pollinators. Besides the associations identified here, the ecology and evolution of plant-pollinator interactions in high-altitude vegetation of the Atlantic Forest remain poorly understood, making urgent the development of an integrative research program, as well as projects on issues related to climate change and biodiversity conservation.
Plant-pollinator interactions in highland vegetation in the atlantic forest
Keywords: Atlantic forest; Montane forest; Pollination; Rocky outcrops; Upper montane forest